2010
DOI: 10.1111/j.1439-0434.2009.01603.x
|View full text |Cite
|
Sign up to set email alerts
|

URP-based DNA Fingerprinting ofBipolaris sorokinianaIsolates Causing Spot Blotch of Wheat

Abstract: Spot blotch, caused by the pathogen Bipolaris sorokiniana is an important disease of wheat and is responsible for large economic losses world wide. In this study, molecular variability in B. sorokiniana isolates collected from different regions of India was investigated using URP-PCR technique. All the 40 isolates used in the study were pathogenic when tested on susceptible host, Agra local, although they varied in pathogenicity. Isolate BS-49 was least virulent showing 4.5 infection index while BS-75 was the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 20 publications
1
38
0
Order By: Relevance
“…Most of the studies on population genetics of R. solani or other plant pathogens using dominant markers such as RAPD, URP, AFLP or ISSR have reported that geographic location or host specificity or both had an effect on population structure (Aggarwal et al 2010;Duncan et al 1993;Jana et al 2005;Stodart et al 2007). Because of the limitations of dominant markers, these studies are difficult to compare with other studies where co-dominant markers (microsatellites) were used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies on population genetics of R. solani or other plant pathogens using dominant markers such as RAPD, URP, AFLP or ISSR have reported that geographic location or host specificity or both had an effect on population structure (Aggarwal et al 2010;Duncan et al 1993;Jana et al 2005;Stodart et al 2007). Because of the limitations of dominant markers, these studies are difficult to compare with other studies where co-dominant markers (microsatellites) were used.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the degree of polymorphism indicated by the percent of polymorphic loci generated and Shannon's index, URP2R was more suitable for studying genetic diversity in populations of both subgroups. In general, both URP and ISSR marker systems have been useful for evaluating variation in fungal populations (Aggarwal et al 2010;Jana et al 2005;Kiyosi et al 2005;Sharma et al 2005;Stodart et al 2007). The UPGMA dendrogram showed two main clusters separating subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…The same 12 URP-PCR primers as used in the present study were used to characterize of B. sorokiniana from India; only two of these primers failed to produce amplification products and one primer produced monomorphic fragments that could be used as molecular markers (Aggarwal et al, 2010). Here, we observed that isolates from Brazil were more efficiently amplified with URP primers and different behavior was observed in isolates from other countries.…”
Section: Discussionmentioning
confidence: 52%
“…using URP-PCR. In contrast, in a study of B. sorokiniana isolates from India, Aggarwal et al (2010) observed a polymorphic profile among the isolates and only two URP-PCR primers were able to amplify monomorphic bands in this phytopathogen. The aim of the present study was to assess the genetic diversity of monoconidial isolates of B. sorokiniana using URP-PCR assays.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation